Analisis Pengelolaan Anggaran Dana Desa BLT pada Masa Pandemi Covid-19 Tahun 2020 Desa Jaharun B - Putri Maulya; Yenni Samri Juliaty Nasution; Laylan Syafina (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the management of the village fund budget for Direct Cash Assistance (BLT) for village communities during the Covid-19 pandemic in Jaharun B Village, Galang District, Deli Serdang Regency. The type of research used in this research is descriptive research using a qualitative approach. The subject of this research is Jaharun B Village, Galang District, Deli Serdang Regency, which is located at Jl.Pertumbukan, Jaharun B Village, Galang District, Deli Serdang Regency. Data collection techniques in this study used observation and interview methods. The results of the first study showed that the Management of Village Funds Direct Cash Assistance (BLT) in Jaharun B Village, Galang District, Deli Serdang Regency, had been carried out according to local government criteria. The results of the second study showed that the distribution of Village Funds Direct Cash Assistance (BLT) had been carried out once a month in cash which was directly given to the BLT-Dana Desa recipients at the village hall. The results of the third study showed that Village Fund Management was optimal from an economic point of view An Islam that is transparent, responsible,and fair.